The role of acetylsalicylic acid in the treatment of diseases caused by atherosclerosis - I. S. Yavelov («REMEDIUM GROUP» Ltd., 2023)
Arterial involvement in atherosclerosis is systemic in nature and is not limited to a single vessel causing ischemic symptoms. Atherosclerotic plaques at various stages of development are simultaneously present in arteries of a patient with atherosclerosis, and many of them undergo cycles of rupture and repair without any clinical manifestations. The chronic use of antithrombotic drugs is one of the ways to prevent the development of clinically significant thrombosis after atherosclerotic plaque destabilization. For this purpose antiplatelet agents, are used in patients with diseases caused by atherosclerosis, who do not have indications for long-term use of high (therapeutic) doses of anticoagulants. At present, acetylsalicylic acid maintains a leading position of the main antithrombotic drug in monotherapy and a must component of composite antithrombotic therapy. Recent studies have limited its role only in certain clinical settings: (1) a prolonged (more than 1 month) use after coronary stenting in patients requiring a long-term use of high (therapeutic) doses of oral anticoagulants; (2) a long-term use after coronary stenting in some patients receiving acetylsalicylic acid combined with ticagrelor; (3) use as first-line drug monotherapy in patients with symptomatic atherosclerosis of arteries of the lower extremities; (4) a long-term use as first-line drug monotherapy after ischemic non-cardioembolic stroke. The use of acetylsalicylic acid requires adequate patient adherence to treatment and sufficient bioavailability of the active substance. When there are doubts on proper bioavailability, it is reasonable to use nonenteric-coated dosage forms of acetylsalicylic acid.